Flora's very windy day - Birdsall, Jeanne; Phelan, Matt. (New York Clarion Books, 2010)
When a big wind blows her annoying little brother away, Flora decides to save him despite the many tempting offers she gets for him from, among others, a cloud, an eagle, the man in the moon, and the wind itself.
Keywords: Brothers and sisters -- Juvenile fiction; Winds -- Juvenile fiction; Brothers and sisters -- Fiction; Winds -- Fiction